GRAMMATICAL COHESION IN THAI CAVE RESCUE NEWS IN INTERNATIONAL NEWSPAPERS - Rika Wahyuni Tambunan; Ridwan Hanafiah; Umar Mono (Universitas Bengkulu, 2019)
This research aimed to identify the types of grammatical cohesion, as well as to describe the realizations of grammatical cohesion used in international newspapers. The data of this research were clauses, phrases, and words. This study departed from the theory of grammatical cohesion from Halliday & Hasan (1976) and the theory of conjunctive system by Halliday & Matthiesen (2014). The sources of data were Thai Cave Rescue news in British Broadcasting Corporation, Russia Today, France 24, Voice of America and China Central Television newspapers. The method used in this research was qualitative. It provided the types that reference (43%) was predominant with personal and comparative reference, was realized by anaphoric and cataphoric. Conjunction (42%) with the additive, temporal, adversative, matter, clarifying, conditional, varying and cause conjunction, was realized by the conjunctive system. Substitution (10%) with nominal and verbal substitution was realized by replacing one item by another. Ellipsis (5%) with clausal and nominal ellipsis, was realized by eluding a noun, verb or clause and recovering it by referring to an element in the preceding text. The finding revealed that the news texts seldom use other types of the grammatical cohesion especially the use of ellipsis and substitution which were possible to be used in writing because most researchers stated that both ellipsis and substitution were commonly found in speaking.Keywords:grammatical cohesion, Thai cave rescue news, international newspaper